2019
DOI: 10.1177/1758573219869335
|View full text |Cite
|
Sign up to set email alerts
|

Distal clavicle autograft for anterior-inferior glenoid augmentation: A comparative cadaveric anatomic study

Abstract: Introduction The aim of this study was to anatomically compare distal clavicle and coracoid autografts and their potential to augment anterior-inferior glenoid bone loss. Methods Ten millimeters of distal clavicle and 20 mm of coracoid were harvested bilaterally from 32 cadavers. Length, weight, and height were measured and surface area and density were calculated. For each graft, ipsilateral measurements were compared and the ability to restore corresponding glenoid bone loss was calculated. Results Distal cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…19,26 Our study found that the distal clavicle autograft (DCP and DCR) provided a slightly larger surface area than the SLJ (309.25 vs 302.84 mm 2 , respectively), consistent with the literature. Hudson et al 10 found that the distal clavicle yielded significantly more graft than the coracoid. The surface area of the articular distal clavicle and the superior distal clavicle were nearly twice that of the lateral coracoid, allowing the grafted distal clavicle to potentially fill larger glenoid defects—particularly defects >25% of the glenoid—and restore a more native glenoid articular surface compared with coracoid transfer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19,26 Our study found that the distal clavicle autograft (DCP and DCR) provided a slightly larger surface area than the SLJ (309.25 vs 302.84 mm 2 , respectively), consistent with the literature. Hudson et al 10 found that the distal clavicle yielded significantly more graft than the coracoid. The surface area of the articular distal clavicle and the superior distal clavicle were nearly twice that of the lateral coracoid, allowing the grafted distal clavicle to potentially fill larger glenoid defects—particularly defects >25% of the glenoid—and restore a more native glenoid articular surface compared with coracoid transfer.…”
Section: Discussionmentioning
confidence: 99%
“…8 The distal clavicle autograft is gaining further attention as a graft source. 10,19,25 Biomechanical studies have shown the distal clavicle to be comparable with the coracoid in terms of contact area and mean and peak pressure. 19 Resection of 1 cm medial to the distal end of the clavicle has been shown to be sufficient to reconstruct a 25% vertical glenoid defect.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Distal clavicle has a broader radius of reconstruction than that of a coracoid graft [ 66 ] but, on the other hand, had greater variability and lower density than coracoid grafts [ 67 ].…”
Section: Surgical Management Of Glenoid Defectsmentioning
confidence: 99%